Health-related quality of life among patients with cirrhosis at a tertiary care center in Addis Ababa, Ethiopia: a cross-sectional study - Zewde, Edgeit Abebe; Teklemariam, Awgichew Behaile; Ayele, Tesfaneh Shemeles; Agidew, Melaku Mekonnen; Mulu, Anemut Tilahun; Melaku, Metages Damtie (Frontiers in Gastroenterology, 2024)
BackgroundHealth-related quality of life (HRQoL) reflects an individual’s perception of how disease and treatment affect their physical, functional, emotional, and social well-being. The burden of cirrhosis is high in Ethiopia but reports on HRQoL among cirrhosis patients are lacking. This study aimed to assess HRQoL and associated factors among patients with cirrhosis at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia.MethodsA cross-sectional study was conducted among 221 patients with cirrhosis at Tikur Anbessa Specialized Hospital. Data were coded and entered into Epi Data 4.6.0.2 and analyzed by STATA software version 17m/p. Bivariable and multivariable linear regression analyses were performed. A p-value lower than 0.05 was used to declare statistical significance.ResultsThe mean ± SD age was 42.74 ± 12.25. In multivariable linear regression analysis, Mid Upper Arm Circumference (MUAC) (Standardized β.coff (Std.β.coff) = 0.12, 95% CI (0.06, 0.18), age ≥50 (Std.β.coff = -0.38, 95% CI (-0.68,-0.09), Child-Turcotte-Pugh (CTP) class B (Std.β.coff = -0.92, 95% CI (-1.28, -0.55), CTP class C (Std.β.coff = -1.69, 95% CI (-2.30,-1.07) were significantly associated with mean quality of life score.ConclusionQuality of life score was significantly associated with age, CTP class, and MUAC. Health-related quality of life should be taken into consideration in the assessment and treatment of patients with cirrhosis. Older patients, patients with decompensated cirrhosis, and patients with lower MUAC measurements should be given special attention.